Three Years in the Life of a Peer Support Initiative for Graduate Students Studying Adult Learning and Leadership – an Action Research Project Implementing the “ALL Peer Connect Project” - Jeanne E. Bitterman; Yoshie Tomozumi Nakamura; Zachary Van Rossum; Sultana Mustafa (Adult Education Research Conference, 2012)
The purpose of this action research study is to explore and understand the perceived impacts of a three year peer support initiative on graduate students‘ academic and professional experience and how this initiative can potentially contribute to the development of a community of practice among graduate students. The peer connect program, also referred to as ―Connect ALL‖ was started in the fall semester of 2009 in Adult Learning and Leadership (ALL), a non-cohort program at Teachers College, Columbia University. Under this initiative, each newly admitted student joining the master‘s or doctoral program is matched with a current student or an alumnus, referred to as the ―connector,‖ who assists the newer student, or ―connectee,‖ with negotiating the program and other academic needs. Participation in the program is voluntary. The intent of the program is to expand the peer network and aid students‘ successful integration into the field of Adult Learning and Leadership.